2008
DOI: 10.1111/j.1750-3639.2007.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH ARTICLE: Myelin Abnormalities without Oligodendrocyte Loss in Periventricular Leukomalacia

Abstract: The cellular basis of myelin deficits detected by neuroimaging in long-term survivors of periventricular leukomalacia (PVL) is poorly understood. We tested the hypothesis that oligodendrocyte lineage (OL) cell density is reduced in PVL, thereby contributing to subsequent myelin deficits. Using computer-based methods, we determined OL cell density in sections from 18 PVL and 18 age-adjusted control cases, immunostained with the OL-lineage marker Olig2. Myelination was assessed with myelin basic protein (MBP) im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
213
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 230 publications
(233 citation statements)
references
References 54 publications
18
213
2
Order By: Relevance
“…We also found evidence of axonal injury in the corpus callosum in our model, similar to recent reports from autopsy cases of PVL (Billiards et al, 2008). Therefore, an alternative hypothesis can be offered here: The process of final differentiation and myelin synthesis of OPCs is orchestrated by a complex interaction between axons and these cells (Bozzali and Wrabetz, 2004).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also found evidence of axonal injury in the corpus callosum in our model, similar to recent reports from autopsy cases of PVL (Billiards et al, 2008). Therefore, an alternative hypothesis can be offered here: The process of final differentiation and myelin synthesis of OPCs is orchestrated by a complex interaction between axons and these cells (Bozzali and Wrabetz, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…These cells are prominent during the peak period of PVL (i.e., between 24 and 32 weeks gestational age) (Back et al, 2007). There are also data suggesting that surviving OPCs undergo maturational arrest in PWMI lesions: a recent autopsy study of premature infants detected numerous morphologically immature Olig-2-positive cells in PVL lesions, indicative of arrested differentiation (Billiards et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, we found that a proportion of CD68-immunopositive cells expressed the marker Ki67 in the PVWM of the hemorrhage brains, indicating that proliferation contributes at least to a minor degree to the increased number of microglia. Our findings, however, support previous human studies in which a quick recruitment, migration, and transformation of microglia of hematopoietic origin to CD68-expressing microglia was suggested as being the main mechanism for the enhanced number of microglia (27). It is unclear how quickly CD45-immunopositive microglia There was evidence of increased apoptosis in the PVWM of the hemorrhage group, and with increased severity there was increased cell apoptosis, which was associated with axonal injury in the PVWM.…”
Section: Discussioncontrasting
confidence: 33%
“…It looked as if new oligodendrocyte precursors were migrating to the site of the injury to replace cells that had been destroyed by the stroke 4 . But something was stopping the precursors from developing into oligodendrocytes that produce myelin.…”
Section: Formative Yearsmentioning
confidence: 99%